IMUNOMODULATOR DARI HERBAL - Muhammad Walid; Luluk Izzati (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2021)
Years 2019 the world attended the introduction of a disease caused by a virus corona. The case of the virus corona entered indonesia to third on sunday january 2020.Since then the indonesian government responded to an emergency in march 2020.Before being discovered a vaccine to prevent the disease, people drinking, antibiotics ibuprofen for the pain and vitamin.However in addition to the use of, the village community bandengan pekalongan city use of herbs to boost immunity. Body They are consuming it in the form of herbal medicine among others appointment Temu ireng ( curcuma aeroginosa ), Jinten ( Cuminum cyminum ), Mengkudu (Morinda citrifolia ). Jahe ( Zingiber officinale ), usually they use as the heat on the body and made in the form of a hot drink.The public believe with increasing stamina and a disease caused by a virus corona wo not happen. Keywords : Imunomodulator, Herbal, Stamina